2010
DOI: 10.1111/j.1743-6109.2009.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Profile of the Expression of Thyroid Hormone Receptors in Rat and Human Corpora Cavernosa of the Penis

Abstract: IntroductionIn the last few years, various studies have underlined a correlation between thyroid function and male sexual function, hypothesizing a direct action of thyroid hormones on the penis.AimTo study the spatiotemporal distribution of mRNA for the thyroid hormone nuclear receptors (TR) α1, α2 and β in the penis and smooth muscle cells (SMCs) of the corpora cavernosa of rats and humans during development.MethodsWe used several molecular biology techniques to study the TR expression in whole tissues or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
0
28
0
2
Order By: Relevance
“…(2, 612, 122)]. Recently, Flood et al (12) performed an in silico analysis of the promoter of several enzymes and receptors involved in both the androgen and TH axes.…”
Section: Ths and Androgens In The Gonadsmentioning
confidence: 99%
“…(2, 612, 122)]. Recently, Flood et al (12) performed an in silico analysis of the promoter of several enzymes and receptors involved in both the androgen and TH axes.…”
Section: Ths and Androgens In The Gonadsmentioning
confidence: 99%
“…The presence of TRs and TSHR in the smooth musculature and corpus cavernosum of the clitoris, as well as in the glial cells of the dorsal nerve of the clitoris has not been previously approached in any species. In contrast, TRα and ß have been identified in the corpus cavernosum of the penis (46). Both hypo and hyperthyroidism are related to impotence in males by affecting the contraction of the corpus cavernosum and smooth muscle of the penis (47)(48).…”
Section: Discussionmentioning
confidence: 89%
“…The presence of thyroid hormone receptor isoforms in the male genital tract may be a further mechanism of action of that relationship. Carosa et al (2010) demonstrated the presence of TRa1, TRa2, and TRb in rat and human corpus cavernosum. TRa1 and TRa2 both expressed in the penis and smooth muscle cells during ontogenesis without-dependent changes TRb remained high in adulthood and its expression is regulated by development.…”
Section: Thyroid and Prolactin Hormonementioning
confidence: 87%